Conceptual Engineering and Parrhesia: To the Problem of Managing Subjectivity - Natalya Yu. Kozlova (RUDN Journal of Philosophy)
The study examines conceptual engineering and its connection with the rhetoric of science and parrhesia. It is argued that the normative-revisionist orientation of conceptual engineering, expressed in the criticism of concepts and the comprehension of the possibilities of their productive semantic correction or replacement, testifies to its claim to manage meaning through language control. Such an attitude reveals features of a rhetorical strategy in the concept: analyzing “problematic” discussion contexts, conceptual engineering strives to “program” correct ideas and representations that eliminate injustice and improve social and political relations, that is, it rather rhetorically matches linguistic possibilities and communicative-situational goals. It is shown that the connection between the political and issues of knowledge permeates the problematic field of conceptual engineering and, given the focus of the direction on the transformation of social and political relations by changing intellectual and semantic strategies, is formalized in the question of the formation of subjectivity and its management. The complexity of the tasks pursued by conceptual engineering is demonstrated by the example of the analysis of parrhesia - the ancient philosophical technique of “free speech” aimed at the transformation of subjectivity. Three dimensions of parrhesia are considered: political, ethical and philosophical; the dynamics of their formation and interrelation are traced. An analysis of the conceptual foundations of the confrontation between the sophistic and Socratic-Platonic traditions of understanding rhetoric and its role in the development of parrhesia is carried out. It is shown how, under the pressure of epistemological problems, the idea of “ethics of speech” arises, which leads to a shift in the emphasis in the idea of parrhesia from the political right to express an opinion to the duty of self-management preceding any statement - for the sake of the right to address others and manage them. The result of the analysis of the three dimensions of parrhesia is the conclusion according to which the management of subjectivity is not just manipulation of the subject’s opinion, but a complex, ethically regulated process of transforming his deep convictions and values. It is substantiated that for modern conceptual engineering, the analysis of parrhesia is relevant in that it problematizes aspects of the management of meaning and subjectivity that are overlooked by the developers of the direction.